O uso da ludicidade no ensino e aprendizagem de Geografia na Educação Básica: um estudo de caso - CARVALHO, Luana Valente (2021)
In the last decades, the teaching of geography has been having significant transformations of new technologies, which could have detached the geography teacher from the use of more ludic methodologies, simple and easy to use. The objective of this proposal is to investigate the insertion of ludic activities in the school environment, in a case study in the Isabel Amazonas State Elementary and High School (E.E.E.F.M ISAM), Ananindeua-PA, to hypothesize about the viability of its use in the classroom. The methodological proposal used in this research was quantitative because there is a relationship between the subject and the object, in which knowledge, the object, and the researcher are integral and dependent parts, where the aspect of reality is sought by focusing on understanding and explaining the dynamics of social relations in the school environment. However, it was intended the insertion of more dynamic, creative, and stimulant didactic models beyond the textbook and expositive classes by contributing to the process of inclusion of students with and without disabilities in the educational environment through the use of ludic methodologies as building scale models, the role of the geography teacher, in the incorporation of the development of ludic activities in the classroom.